PEMBINAAN USAHA KECIL MENENGAH DALAM PEMBUATAN SABUN COLEK DI TEMBESI TOWER KELURAHAN TEMBESI - Hazimah Hazimah; Zefri Azharman (ASOSIASI IDEBAHASA KEPRI, 2021)
UKM (small and medium enterprises) in the Tembesi Tower, Tembesi sub-district, are not developing well. This is indicated by the low turnover obtained by each UKM (small and medium enterprise) in 1 month. customer expectations. New products must be made so that these small and medium businesses can survive and continue to exist. The new product must have a distinctive and good quality so that the product positioning is clearer and able to compete with other products on the market. This service activity aims to provide a solution to this by creating a new product in the form of a dab soap that is safe for health and environmentally friendly. Some soaps circulating in the market only prioritize cleaning power, but the chemical content in the soap is harmful to health and the environment. The impact of conventional soap on health is irritation of the skin which, if left for a long time, the irritation will turn into eczema. In addition, conventional soap also harms the environment because the raw material for soap comes from petroleum which is difficult to be broken down by bacteria. Community service activities are carried out in the form of coaching. The service team expects to increase the income and advantages of UKM (small and medium businesses) in the Tembesi Tower and to be able to create jobs or open a business with a revolutionary cream soap product design.